The Relationship Between Islam and Local Wisdom in the Kampung Naga Tradition: Living Sunnah Research - Wahyudin Darmalaksana; Teti Ratnasih; Saifudin Nur (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This study aims to analyze the values of the hadith of the Prophet who lived in the Kampung Naga tradition. This study applies a qualitative approach with a descriptive-analytical method through a field study based on the interpretation of the living sunnah. The results and discussion of this study found that the living sunnah in the Kampung Naga tradition lies in the rituals of pregnant women, birth of children, circumcision, gusaran, marriage, inheritance, blessings, death prayers, Hajat Sasih after Eid prayer, and others. The study concludes that the living sunnah is relevant to be applied considering that the Kampung Naga tradition is a crystallization of Islam and Sundanese local wisdom as an ancestral heritage. Living sunnah is able to explore the values of hadith that live in the Kampung Naga tradition without syncretic stigmatization of rituals that are considered incompatible with Islamic law. This study recommends further research maximally by compiling the research themes of living sunnah in the Kampung Naga tradition.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//